Experimental Research on Triple Blended Self-Compacting Geo Polymer Concrete - Srinivas Prabhu, R.; Anuradha, R.; Vivek, S. (Asian Journal of Engineering and Applied Technology, 2016)
Self-compacting concrete (SCC) represents one of the most outstanding advances in concrete technology during the last decade. self compacting concrete is a flowing concrete mixture that is able to consolidate under its own weight. The highly fluid nature of SCC makes its suitable for placing in difficult situation and in sections with congested reinforcement. The aim of the study is to make use of Fly Ash, Ground Granulated Blast Furnace Slag and Silica Fume as replacements of cement and understand its effect on the fresh properties and hardened properties of concrete. The investigation includes the concept of triple blending of Fly ash, GGBS and Silica Fume, this triple blend exploits the beneficial characteristics of Pozzolanic materials in producing a better concrete.